3469 Age and racial variation in the relation between blood lead level and asthma in children: Data from National Health and Nutrition Examination Survey 1999-2016. (27th March 2019) - Shaheen, Magda; Pan, Deyu
Abstract : OBJECTIVES/SPECIFIC AIMS: Lead (Pb) exposure can seriously affect nervous system and kidney. Young children are vulnerable to Pb exposure. However, the role of low-level Pb exposure in asthma in children and the age and racial disparity is not well studied. The objectives are to examine the relation between Pb level and asthma status and to determine the age and racial/ethnic differences in this relation. METHODS/STUDY POPULATION: We analyzed data from National Health and Nutrition Examination Survey 1999-2016 for 22, 885 children 1-15 years old. Asthma information was collected by questionnaire. Blood lead level was measured using mass spectrometry. The association between blood Pb level and asthma status was assessed by logistic regression after adjusting for children' age, gender, race/ethnicity, insurance status, and source of care; household poverty, mother's age and smoking status. Data were analyzed using Stata 14 considering design and sample weight and p<0.05 is statistically significant. RESULTS/ANTICIPATED RESULTS: Pb level was associated with asthma status (Adjusted Odds Ratio (AOR)=1.4, 95% Confidence Interval (CI) = 1.2-1.7, p < 0.001). Stratified analysis by age showed that blood Pb level is related to asthma only in children 1-5 years old (AOR = 1.3, 95% CI = 1.1-1.5, p = 0.004). There was no racial/ethnic difference in this association. DISCUSSION/SIGNIFICANCE OF IMPACT: Pb level is associated with asthma status in children especially young children. Health risk of low Pb is a concern. Preventive measures by reducing potential sources of Pb should be introduced early.